Tree identity and diversity directly affect soil moisture and temperature but not soil carbon ten years after planting. Issue 1 (12th January 2022) - Martin‐Guay, Marc‐Olivier; Belluau, Michaël; Côté, Benoit; Handa, Ira Tanya; Jewell, Mark D.; Khlifa, Rim; Munson, Alison D.; Rivest, Maxime; Whalen, Joann K.; Rivest, David
Abstract: Soil C is the largest C pool in forest ecosystems that contributes to C sequestration and mitigates climate change. Tree diversity enhances forest productivity, so diversifying the tree species composition, notably in managed forests, could increase the quantity of organic matter being transferred to soils and alter other soil properties relevant to the C cycle. A ten‐year‐old tree diversity experiment was used to study the effects of tree identity and diversity (functional and taxonomic) on soils. Surface (0–10 cm) mineral soil was repeatedly measured for soil C concentration, C:N ratio, pH, moisture, and temperature in twenty‐four tree species mixtures and twelve corresponding monocultures (replicated in four blocks). Soil pH, moisture, and temperature responded to tree diversity and identity. Greater productivity in above‐ and below‐ground tree components did not increase soil C concentration. Soil pH increased and soil moisture decreased with functional diversity, more specifically, when species had different growth strategies and shade tolerances. Functional identity affected soil moisture and temperature, such that tree communities with more slow‐growing and shade‐tolerant species had greater soil moisture and temperature. Higher temperature was measured in communities with broadleaf‐deciduous species compared to communities with coniferous‐evergreen species. We conclude that long‐term soil C cycling in forest plantations will likely respond to changes in soil pH, moisture, and temperature that is mediated by tree species composition, since tree species affect these soil properties through their litter quality, water uptake, and physical control of soil microclimates. Abstract : Soil abiotic properties were affected by tree diversity and identity. Tree composition had indirect effects on soil carbon through soil microclimate.